How the co-design, use, and refinement of an instructional model emphasizing argumentation relates to changes in teachers' beliefs and practices. Issue 14 (22nd September 2022) - Enderle, Patrick; Grooms, Jonathon; Sampson, Victor; Sengul, Ozden; Koulagna, Yotah
ABSTRACT: We examine how a unique professional learning experience for teachers, which consists of an opportunity to (a) co-design a new instructional model intended to give students opportunities to participate in scientific argumentation, (b) develop instructional materials based on the new model, and then (c) use the materials inside their classrooms, is related to changes in teacher beliefs and teaching practices over time. These cases suggest participation in this type of professional learning experience altered these teachers' beliefs and these changes were guided by their experiences inside the classroom when teaching lessons with these new instruction materials. Our findings indicate that teacher reflection on their instructional decisions and the nature of student activity during lessons using the materials had a great influence on the beliefs and practices of these teachers. The implications of this finding suggest that an opportunity to develop instructional materials during a professional learning experience can foster a context for teachers to think about teaching and learning in new ways but any real change in teacher thinking and practices requires teachers to (a) use the materials they develop and then (b) problematise their current instructional practices.